Artificial Chemical Nuclease and Cytotoxic Activity of a Mononuclear Copper(I) Complex and a Related Binuclear Double-Stranded Helicate - Pavez-Irrazabal, J; Pavez-Irrazabal, J; Lemus-Chavez, L; Lemus-Chavez, L; Silva-Molina, C; Silva-Molina, C; Levín-Vásquez, P; Levín-Vásquez, P (John Wiley and Sons Inc, 2021)
Copper complexes are promising candidates for anticancer drugs, because of their redox properties and the ability to generate ROS (reactive oxygen species) in the cellular media. Most of the reported complexes with anticancer properties are based on Cu(II), which must be reduced to Cu(I) to exert the therapeutic action. Here, we report on the synthesis and characterization of two novel copper(I) complexes, a mononuclear complex [Cu(L1)2](ClO4) (1) and a binuclear helicate [Cu2(L2)2](ClO4)2 (2) (L1=2-ethoxy-1,10-phenanthroline, L2=1,2-bis((1,10-phenanthrolin-2-yl)oxy)ethane), which were designed to be structurally comparable, in order to evaluate the effect of nuclearity on the artificial nuclease activity. The activity of helicate (2) was higher than that of the monometallic (1), and the DNA cleavage mechanism is through the generation of hydroxyl radical in a Fenton-like reaction, which occurs after oxidation of Cu(I) by O2. Also, helicate (2) showed a higher cytotoxic effect against different cancer cells lines, while both complexes are more active than cisplatin. © 2021 Wiley-VCH GmbH